Evolution, Development and Ecology of Anemonefishes Model Organisms for Marine Science - Laudet, Vincent; Ravasi, Timothy (Taylor & Francis, 2023)
Anemonefishes, one of the most popular and recognizable of fishes in the world, are much more than film characters; they are also emerging model organisms for studying the biology, ecology, and evolution of coral reef fishes. They are a group of 28 species often employed to study patterns and processes of social organization, intra- and inter-specific competition, sex change, mutualism, dispersal and connectivity of fish populations, habitat selection, pigment pattern formation, lifespan and predator-prey interactions. This multi-authored book covers all these areas and provides an update on the research done with this model and the perspective it opens for the future. Key Features Contains basic and up-to-date information on an emerging fish model Allows non-specialist readers to grasp the relevance of a wide research area Provides accurate and easy to access information on each of the 28 species Includes guidance for establishing a breeding colony Documents that anemonefishes are useful model organisms for ecological, developmental and climate research The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.